Factors affecting english oral communication among Malaysian civil engineering graduates an exploratory analysis - Palpanadan, Sarala @ Thulasi; Ahmad, Iqbal (IAEME Publication, 2018)
This study examined the factors affecting English oral communication skills among the civil engineering graduates in Malaysia. The purpose of this study was to explore the crucial challenging factors faced by graduates the in speaking in English. A survey technique was used to collect data from 150 civil engineering graduate of a university in Malaysia. The data was analyzed using descriptive statistics and factor analysis. Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy value was .907 (highly significant). The factor analysis showed that there were four prime factors: lack of practice, poor readings habits, poor vocabulary and cramming habits. This study also provided some suggestions to improve their oral communication skills.